IMPLEMENTASI PROGRAM JADEK (JAUH JADI DEKAT) DALAM PEMBUATAN e-KTP DI DESA MANDIREJO KECAMATAN MERAKURAK KABUPATEN TUBAN - Zana Malinda Clarissa; Suci Megawati (Universitas Negeri Surabaya, 2022)
Jadek Program (Jauh So Dekat) is a population administration service program of the Population and Civil Registry Office of Tuban Regency that is used to bring services closer to the community through online means, namely verification, entry and file scan only through the Village. This research aims to find out and analyze the implementation of jadek program as access to population administration services in the issuance of e-KTP at the Office of Population and Civil Registration, one of which is in Sumurgung Village and Mandirejo Village. The type of research used is qualitative deskriftif using implementation theory according to David C. Korten (1998). Data collection techniques are used in interviews and observations with purposive samplingtechniques. The data sources in this study used primary data and secondary data. Data analysis techniques are performed using miles and huberman models, namely data reduction, data presentation, and conclusion withdrawal. The results showed that in the program indicator there has been a conformity between jadek program and target group. In the indicators of the implementing organization there is no conformity between the Jadek program and the jadek program implementation organization. In the target group indicator there is no conformity between the community and the implementing organization. Keywords : Implementation, Jadek (Jauh Jadi Dekat) Program, e-KTP